Empowering Women in Giving Moringa Biscuits to Prevent Anemia to Pregnant Women in Jatinom Village - Agustina, Ika; Sari, Levi Tina; Ulfa, Maria; Noviasari, Ita; Monica, Laily Prima; Kusnianto, Maratus Sholichah Fitriah Hajar; Handayani; Wibisono, Wahyu (STIKes Patria Husada Blitar, 2023)
Anemia in pregnancy was still one of the main health problems in Indonesia, the main cause of anemia in pregnant women was a lack of nutrients needed for erythrocyte synthesis, especially iron, folic acid and vitamin B12. One complete prevention of anemia was by gives moringa biscuits which can be consumed by pregnant women as an additional food or complementary food. The method used in implementation this community service was through 2 activities. The first activity was provided education to Jatinom posyandu cadres, Blitar Regency. The second activity was trained in make a Moringa biscuits. The results of the service showed that the knowledge of service participants before provided education was 50% cadres in the poor category, 30% cadres in the sufficient category, and 20% cadres in the good category. Knowledge after being given education was 80% cadres with good knowledge and 20% cadres with sufficient knowledge. Increasing health cadres' knowledge about anemia prevention will create positive rights for pregnant women because health cadres' knowledge will be transformed to pregnant women in their area. Apart from being transformed, health cadres will also support and accompany pregnant women in implemented anemia prevention. It was hoped that this will reduce the rate of anemia in pregnant women.